Burden of disease due to cancer in Spain - Pérez-Gómez Beatriz; Gil Ángel; Gènova-Maleras Ricard; Morant-Ginestar Consuelo; Álvarez-Martín Elena; Fernández de Larrea-Baz Nerea; López-Abente Gonzalo (BMC, 2009)
Abstract Background Burden of disease is a joint measure of mortality and morbidity which makes it easier to compare health problems in which these two components enjoy different degrees of relative importance. The objective of this study is ascertaining the burden of disease due to cancer in Spain via the calculation of disability-adjusted life years (DALYs). Methods DALYs are the sum of years of life lost due to premature mortality and years lost due to disability. World Health Organization methodology and the following sources of data were used: the Mortality Register and Princeton Model Life Table for Years of life lost due to premature mortality and population, incidence estimates (Spanish tumour registries and fitting of generalized linear mixed models), duration (from data of survival in Spain from the EUROCARE-3 study and fitting of Weibull distribution function) and disability (weights published in the literature) for Years lost due to disability. Results There were 828,997 DALYs due to cancer (20.5 DALYs/1,000 population), 61% in men. Of the total, 51% corresponded to lung, colorectal, breast, stomach and prostate cancers. Mortality (84% of DALYs) predominated over disability. Subjects aged under 20 years accounted for 1.6% and those aged over 70 years accounted for 30.1% of DALYs. Conclusion Lung, colorectal and breast cancers are responsible for the highest number of DALYs in Spain. Even if the burden of disease due to cancer is predominantly caused by mortality, some cancers have a significant weight of disability. Information on 2000 burden of disease due to cancer can be useful to assess how it has evolved over time and the impact of medical advances on it in terms of mortality and disability.